2019
DOI: 10.1021/acs.jpcc.9b03061
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Dependent Hydrazine Adsorption Properties in Few-Layer WS2

Abstract: We have developed a lithography free technique for the fabrication of two-dimensional material based devices for electrical characterization. We fabricated few-layer and multilayer WS2 devices using a transmission electron microscope (TEM) grid as a shadow mask, and its transport characteristics were studied by electrical measurements. WS2 samples were synthesized by first depositing WO3 followed by sulfurization and characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The three-dimensional (3D) AFM height image in Figure d shows that the thickness of FL-WS 2 nanosheets is 6.2 nm; thus, it can be inferred that the layer number is ∼8 by reference to the 0.75 nm thickness of monolayer WS 2 . Furthermore, the Raman spectrum in Figure e reveals that the intensity of the out-of-plane mode (A 1g ) is obviously stronger than that of the in-plane mode (E 2g 1 ), indicating that the layer number of FL-WS 2 nanosheets is more than 3, which is in good agreement with the AFM result . Ultraviolet–visible (UV–vis) spectra were adopted to unveil the optical properties of the FL-WS 2 materials.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The three-dimensional (3D) AFM height image in Figure d shows that the thickness of FL-WS 2 nanosheets is 6.2 nm; thus, it can be inferred that the layer number is ∼8 by reference to the 0.75 nm thickness of monolayer WS 2 . Furthermore, the Raman spectrum in Figure e reveals that the intensity of the out-of-plane mode (A 1g ) is obviously stronger than that of the in-plane mode (E 2g 1 ), indicating that the layer number of FL-WS 2 nanosheets is more than 3, which is in good agreement with the AFM result . Ultraviolet–visible (UV–vis) spectra were adopted to unveil the optical properties of the FL-WS 2 materials.…”
Section: Resultsmentioning
confidence: 94%
“…37 Furthermore, the Raman spectrum in Figure 1e reveals that the intensity of the out-ofplane mode (A 1g ) is obviously stronger than that of the inplane mode (E 2g 1 ), indicating that the layer number of FL-WS 2 nanosheets is more than 3, which is in good agreement with the AFM result. 38 Ultraviolet−visible (UV−vis) spectra were adopted to unveil the optical properties of the FL-WS 2 materials. As shown in Figure 1f, the UV−vis spectrum of FL-WS 2 exhibits three peaks A, B, and C at 635, 527, and 459 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The AFM topography images were obtained in tapping mode in air with the aid of Si tips with a typical tip radius of 25 nm, tip length of ∼240 μm, spring constant range 1.8−12.5 N m −1 , and frequency range 58−97 kHz. The average thicknesses of samples were found to be 2.23, 4.04, and 6.85 nm respectively [83] Figure 5 shows the tunneling I-V characteristic curves of three Graphene/h-BN/Graphene based single tunnel junctions with varying h-BN thicknesses (tunnel barrier widths). All three curves show exponential dependence of the current (I) with the bias voltage (V) at higher voltages.…”
Section: Direct Quantum Tunnelingmentioning
confidence: 99%
“…Detecting hydrazine with high sensitivity is crucial for many industries. Our recent experimental study [28] has found that the electrical resistance of 2D WS 2 layered materials decreases when they are exposed to hydrazine at varying pressures (i.e. varying N 2 H 4 concentration).…”
Section: Introductionmentioning
confidence: 97%
“…While, 3-4 layers of WS 2 showed only partial recovery during desorption. In contrast, multi-layered WS 2 showed a little or no reversibility upon pumping [28]. To shed light into such interesting response behaviors of 2D WS 2 exposed to N 2 H 4 gas molecule, we carried out a comprehensive study at the first principle level.…”
Section: Introductionmentioning
confidence: 99%